Size selective fishing: the effect of size selectivity on the equilibrium yield in the Nile perch fishery of Lake Victoria - Kammerer, Johannes; Gomez, Santiago; Nyamweya, Chrisphine (AWI discussion paper series, 2022)
The Nile perch fishery of Lake Victoria is regulated with a slot size and with restrictions on legal gear sizes. This study provides an assessment of the effectiveness of the the slot size regulation by simulating the Nile perch fishery with a size structured population model where the size preference of the fishery is an input into the model. The model is compared to the size structure of the Nile perch population from three empirical surveys to find agreement between the model, the bottom-trawl and the catch assessment survey, while the hydroacoustic survey predicts a different population structure. The empirical fishing mortality is 2.0% above the value that produces the maximum sustainable yield, given the empirical fishing fleet selectivity. Next to the actual fleet selectivity, three alternatives are simulated to quantify the effect of the selectivity. We find that the annual yield could be increased by 17.7% by sparing fish below 50cm.